Pengaruh Beban Kerja Terhadap Kinerja Karyawan Pada PT. Asuransi Jiwasraya Cabang Manado Kota - Rolos, Jeky K. R.; Sambul, Sofia A. P.; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
The results of research conducted by t-test and also in accordance with the answers of the respondents at the Manado Branch Jiwasraya insurance company the city shows that the presence of influence between the workload against the performance of employees. From the results of the regression analysis explains that the increase or decrease in an employee's performance is not fully portrayed by the variable workload but there are other variables that affect the performance of employees. Based on research results, obtained results of workload and significant negative effect on performance of employees at PT. Asuransi Jiwasraya branch of Manado city, it is clear that if the workload increases, it will reduce the potential performance employees and otherwise declining workloads then it will increase the performance potential of the employees, with the work load as target achievement system, giving guidance and coaching against the prospective new agents until can reduce the potential performance of the employees.Keywords : workload and work performance.